FORMING ANALYSIS OF SELF-REINFORCED POLYPROPYLENE BASED COMPOSITE-ALUMINIUM HYBRID STRUCTURES - Sivakumar, Dhar Malingam (2012)
This study investigates the formability of hybrid structures made of self reinforced polypropylene and aluminium also known as Fibre-Metal Laminates (FML). Comparisons between FML and monolithic aluminium revealed that FML possess better formability characteristics than monolithic aluminium. Moreover FML gives a 27% weight reduction compared to monolithic aluminium. Comparison between FML and monolithic aluminium surface strain results show FML system having a more uniform strain distribution further enhancing the quality of the final part using this class of material. Furthermore the work required to form FML is 30% less than for monolithic aluminium. The experimental results obtained in the present study shows FML systems have the potential to be adapted to high volume production technique of stamp forming.